Middle English Medical Recipes: A Metadiscursive Approach - Quintana-Toledo, Elena (Studia Anglica Posnaniensia, 2010)
This paper seeks to explore Middle English medical recipes from a metadiscursive perspective. This study will draw on Hyland's (2005) metadiscourse model where code glosses, endophoric markers, evidentials, frame markers and transition markers are included in the interactive dimension, and attitude markers, boosters, engagement markers, hedges and self mention are to be found within interactional metadiscourse. I shall apply this framework for the identification and analysis of data in a corpus which comprises a selection of recipes taken from both Middle English Medical Texts (Taavitsainen - Pahta - Mäkinen 2005) and The corpus of early English recipes. The metadiscursive approach to the study of medical recipes will allow us to establish links between authors, texts and audience of the recipe genre and, consequently, to affirm their status as products of social engagement.